Hegel and Aristotle - Ferrarin, Alfredo, 1960- (Modern European philosophy., 2001)
"This book offers an account of Hegel's idealism and in particular his notions of reason, subjectivity, and teleology, in light of Hegel's interpretation, discussion, assimilation, and critique of Aristotle's philosophy. It is an analysis comparing Hegelian and Aristotelian views of system and history; being, metaphysics, logic, and truth; nature and subjectivity; spirit, knowledge, and self-knowledge; ethics and politics. In addition, Hegel's conception of Aristotle's philosophy is contrasted with alternative conceptions typical of his time and ours."--Jacket